Kemampuan Cognitive Apprenticeship Sebagai Bagian Dari Keterampilan Dasar Mengajar Guru Sekolah Dasar: Cognitive Internship Capabilities as Part of Basic Teaching Skills for Elementary School Teachers - Rezania, Vanda; Nuroh, Ermawati Zulikhatin; Mariyati, Lely Ika (Pedagogia : Jurnal Pendidikan, 2020)
The purpose of this study is to explore further the quality of the basic teaching skills of teachers and the usefulness of students' cognitive apprenticeship abilities that are part of a teacher's basic teaching skills. This study uses a literature review research method that describes theories, findings, and other research materials obtained from reference materials to serve as a basis for research activities to develop a framework for cognitive apprenticeship and basic teaching skills of teachers. The results obtained are that the basic teaching skills of teachers still need to be improved. So we need a breakthrough to help improve the basic skills of teaching teachers, one of which is by applying cognitive apprenticeship skills in the teaching skills of prospective teacher students starting from habituation in lectures.